When Political Will Is Not Enough: Jails, Communities, and Persons With Mental Health Disorders. (January 2016) - Steadman, Henry J.; Morrissey, Joseph P.; Parker, Travis W.
This article describes a project that generated the recommendations of a panel of experts regarding the jail as a venue for the delivery of behavioral health care services. The project was a component of the MacArthur Foundation's Safety and Justice Challenge initiative, which seeks to address over-incarceration by changing the way jails are conceptualized and used. The recommendations were grounded largely in the sequential intercept model that rests on two core principles: minimize the inappropriate penetration of persons with mental illness into the criminal justice system and recognize that the community is the unit of analysis to address criminal justice–mental health problems successfully. Other topics presented in the context of the initiative included bringing the community to scale, jail diversion, the limits of jail responsibility, and the Affordable Care Act's role in providing insurance coverage for detainees.